Developing Interactive Mobile Mathematics Inquiry to Enhance Students’ Problem-solving Skill - Arifin, Moch. Bahak Udin By; Sholeh, Makherus; Hafiz, Abdul; Agustin, Ririn Dwi; Wardana, Mahardika Darmawan Kusuma (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The research aimed to develop interactive multimedia based on scientific inquiry to improve student mathematics problem-solving as a provision for the era of Society 5.0. The research method used is the Agile Method, which is a software development method. This study involved 120 students from the first, second, to third years who were programming mathematics-related subjects at the Madrasah Ibtidaiyah Teacher Education department, Universitas Muhammadiyah Sidoarjo. The results of the development of Interactive Mobile Mathematics Inquiry (IMMI) were valid and proven to improve student problem-solving abilities. In particular, this increase is significant in planning and implementing student plans for a problem. The significance is due to the training in the inquiry aspects during the use of IMMI. The implication of this research in the field of educational technology is that IMMI can be a preliminary study and a pioneer for lecturers, experts, and practitioners to use and further develop IMMI to improve students’ mathematical problem-solving skills at the tertiary level more broadly as preparation for media availability following the values of technological advances in the future Society 5.0 era.